Applied nonparametric econometrics - Henderson, Daniel J.; Parmeter, Christopher F. (Cambridge University Press, 2015)
"Bridging the gap between applied economists and theoretical nonparametric econometricians, this book explains basic to advanced nonparametric methods with applications"-- Provided by publisher.